Pengaruh Pemberian Kolkhisin Terhadap Morfologi dan Jumlah Kromosom Tanaman Binahong(Anredera cordifolia (Ten) Steenis) - Rosida Mahyuni (Jurnal Agroekoteknologi, 2016)
The purpose of the study was to determinethe effect of colchicine on morphology and number of chromosome  of binahong plant (Anredera cordifolia Tenn. Steenis.). The research was conducted at Faculty of Agriculture USUMedan, with a height of 25 metre above sea level, from May until December 2015. The design of the research was a Randomized Block Design of one factor with 5 treatments were: Control (without treatments);0.025% ;0.050%;0.075%;0.100%. Parameters observed were number of leave, weight of fresh shoot per sample, weight of dry shoot per sample, weight of fresh root, weight of dry root and number of chromosome. The results showed that the effect colchicine gave significantly to number of leave, weight of fresh shoot per sample, weight of dry shoot per sample, number  of chromosome : 2n=2x+1=23 set (0.025%), 2n=2x+1=23 set (0.050%), 2n=2x+2=24 set (0.075%) and 2n=2x+4= 26 set (0.100%) with normally chromosome 2n=2x=22 set.   Key words : colchicine, morphology, number of chromosome, binahong plant